Low-carbon corrosion-resistant composite cement and preparation method thereof

By adopting composite technology of low-carbon, high-silicon phase silicate cement and high-silicon iron-rich low-carbon corrosion-resistant cement, combined with fly ash and other materials, the particle size distribution and mineral composition are regulated, the problem that traditional cement concrete is difficult to meet the needs of low-carbonization and long-life under high water pressure and high chloride salt environments is achieved, and high-performance and low-carbon emission composite cement materials are achieved.

CN119612992AActive Publication Date: 2025-03-14WUHAN UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411784458.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-14
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

Traditional cement concrete is difficult to meet the dual needs of low carbonization and long life under high water pressure and high chloride salt environments, and its carbon emissions are high during its production process.

Method used

The low-carbon and high-silicon phase silicate cement clinker and high-silicon iron-rich low-carbon corrosion-resistant cement clinker are combined, combined with materials such as fly ash, building regenerated powder and desulfurized gypsum, and the particle size distribution and mineral composition are regulated through ball milling and airflow grading processes, and the gel structure and mechanical properties are optimized.

Benefits of technology

Under high water pressure and high chloride salt environment, low-carbon corrosion-resistant composite cement exhibits high compressive strength and corrosion resistance, and has stronger resistance to deformation, while achieving the effect of reducing carbon emissions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005173636910000071
    Figure BDA0005173636910000071
  • Figure BDA0005173636910000072
    Figure BDA0005173636910000072
  • Figure BDA0005173636910000073
    Figure BDA0005173636910000073
Patent Text Reader

Abstract

The invention provides low-carbon corrosion-resistant composite cement and a preparation method thereof. In the pretreatment process of ordinary silicate and high-silicon iron-rich phase low-carbon corrosion-resistant cement clinker, according to the characteristics of raw materials, different cement clinker main distribution intervals are concentrated in corresponding intervals of a grading model to achieve a close packing effect, meanwhile, hydration intervals of silicon-phase minerals and aluminum-phase minerals are matched, and the high-silicon iron-rich phase low-carbon corrosion-resistant cement clinker is obtained. More aluminum ions are promoted to enter the gel, the gel structure is optimized, the clinker consumption is reduced, and the overall mechanical property and durability of the material are improved. Through the synergistic excitation effect between the composite reinforcer and the cement hydration product, the hydration degree of the auxiliary cementing material is improved, the pore structure is optimized, the hydration interval of the silicon-phase mineral and the aluminum-phase mineral is further matched, the dosage of cement clinker is reduced, the dosage of the auxiliary cementing material such as the building regenerated micro powder is increased, and the utilization rate of the cement is increased. The effects of reducing carbon and reducing emission are further achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to a low-carbon corrosion-resistant composite cement and a preparation method thereof. Background Art

[0002] With the rapid development of my country's marine economy and the implementation of various major coastal construction projects, the demand for marine concrete has increased year by year. As a country with the largest number of tunnels, the largest construction scale and the fastest development speed in the world, the long-life design of submarine tunnels under high water pressure and high chloride salt environment has become a research focus in my country in recent years. On the other hand, under the guidance of the national strategy of "carbon peak and carbon neutrality", my country is in a critical period of climbing over the low-carbon transformation of energy. It is estimated that carbon emissions from my country's cement concrete industry account for 11% of the country's total carbon emissions, and the production of cement concrete is the main source of carbon emissions, which urgently needs to reduce carbon emissions. In summary, traditional materials cannot solve the dual needs of low carbonization and long life faced by my country's marine concrete. So far, low-carbon corrosion-resistant cementitious materials have become a research hotspot.

[0003] Using industrial solid waste with potential cementitious activity to replace traditional cement to prepare composite cement can not only improve the utilization rate of solid waste, but also reduce material costs, which is an important means of reducing carbon emissions in concrete materials. In addition, with economic development and the continuous advancement of urbanization, China's construction waste discharge in 2020 is about 30×108t. The use of building recycled materials in the preparation of composite cement can not only avoid the landfill of waste concrete, but also reduce the transportation distance and absorb carbon during the storage stage, which has excellent carbon emission reduction capabilities. However, when the incorporation rate of solid wastes such as building recycled micro powder, blast furnace slag, and fly ash is too high, it will affect the performance conditions of composite cement. It is necessary to seek methods and measures to increase the maximum incorporation rate of solid waste on the basis of ensuring the target performance. Therefore, the synergistic preparation method of low-carbon cementitious materials under multiple objectives still needs further research. Summary of the invention

[0004] The main technical problem solved by the present invention is to provide a low-carbon corrosion-resistant composite cement. The low-carbon corrosion-resistant composite cement prepared by the present invention has a 1d compressive strength of ≥32.6MPa, a 28d compressive strength of ≥58.4MPa, and a 28d chloride ion diffusion coefficient of 0.54×10 -12 m 2 / s, 180d seawater corrosion resistance coefficient K 180 ≥1.10, and has stronger ability to resist deformation.

[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0006] In the first aspect, the present invention proposes a low-carbon corrosion-resistant composite cement, comprising the following raw materials in parts by weight: 20 to 25 parts of low-carbon high-silicon phase silicate cement clinker, 30 to 35 parts of high-silicon iron-rich phase low-carbon corrosion-resistant cement clinker, 20 to 25 parts of fly ash, 20 to 25 parts of building recycled micropowder, 0 to 5 parts of desulfurized gypsum, and 0.1 to 1 part of powder composite strengthener.

[0007] Preferably, the low-carbon high-silicon phase silicate cement clinker comprises the following components in mass fractions: 70-80% tricalcium silicate, 5-10% dicalcium silicate, 5-10% tetracalcium aluminoferrite, and 10-20% tricalcium aluminate.

[0008] Preferably, the high-silicon iron-rich phase low-carbon corrosion-resistant cement clinker comprises the following components in mass fractions: 25-30% calcium sulfosilicate, 40-45% calcium sulfoaluminate, 20-25% tetracalcium aluminoferrite, and 5-10% dicalcium silicate.

[0009] Preferably, the powder composite enhancer includes the following components in mass fractions: 50-65% sodium-based desulfurization ash, 30-45% aluminum sulfate, and 5-15% sodium tripolyphosphate;

[0010] The sodium-based desulfurization ash includes the following components in mass fractions: SiO2 0.24%, Al2O3 0.011%, Fe2O3 0.037%, CaO 0.332%, SO3 51.89%, K2O 0.006%, MgO 0.43%, Na2O 43.91%, and LOI 3.36%.

[0011] Preferably, the fly ash includes at least one of ultrafine fly ash, primary fly ash and secondary fly ash.

[0012] Preferably, the particle size of the building recycled micro powder is 50 to 90 μm;

[0013] The building recycled fine powder includes the following components by mass fraction: SiO2 25.26%, Al2O3 5.27%, Fe2O32.02%, CaO 30.81%, SO3 1.35%, K2O 0.14%, MgO 0.43%, Na2O 0.413%, LOI 33.947%;

[0014] The particle size of the fly ash is less than or equal to 4 μm.

[0015] Preferably, the desulfurized gypsum comprises the following components in mass fractions: SiO2 2.6%, Al2O3 0.7%, Fe2O3 0.82%, CaO 43.31%, SO3 40.73%, K2O 0.14%, MgO 0.91%, and LOI 3.36%.

[0016] In a second aspect, the present invention further provides a method for preparing the low-carbon corrosion-resistant composite cement, comprising the following steps:

[0017] Crushing 30 to 35 parts by weight of high-silicon iron-rich phase low-carbon corrosion-resistant cement clinker to a particle size of less than 15 mm to obtain high-silicon iron-rich phase low-carbon corrosion-resistant cement clinker slag;

[0018] crushing 20 to 25 parts by weight of low-carbon high-silicon phase silicate cement clinker to a particle size of less than 15 mm to obtain low-carbon high-silicon phase silicate cement clinker slag;

[0019] The high-silicon iron-rich phase low-carbon corrosion-resistant cement clinker slag is mixed with 0 to 3 parts by weight of desulfurized gypsum to obtain a high-silicon iron-rich phase low-carbon corrosion-resistant cement binary material;

[0020] The low-carbon high-silicon phase silicate cement clinker residue is mixed with 0 to 2 parts by weight of desulfurized gypsum to obtain a low-carbon high-silicon phase silicate cement binary material;

[0021] Adding the high-silicon iron-rich phase low-carbon corrosion-resistant cement binary material into a ball mill, adding a grinding aid, and ball milling to obtain a first cement mixture with a particle size of less than 0.05 mm;

[0022] Adding the low-carbon high-silicon phase silicate cement binary material into a ball mill, adding a grinding aid, and ball milling to obtain a second cement mixture with a particle size of less than 0.03 mm;

[0023] The first cement mixture is classified by an air flow classifier to obtain high-silicon iron-rich phase low-carbon corrosion-resistant cement with two particle size distributions of 15 to 30 μm and 30 to 50 μm;

[0024] The second cement mixture is classified by an air flow classifier to obtain low-carbon high-silicon phase silicate cement with two particle size distributions of 4 to 15 μm and 15 to 30 μm;

[0025] Low carbon corrosion resistant composite cement is obtained by mixing two types of high silicon iron-rich phase low carbon corrosion resistant cement with two types of particle size distribution, two types of low carbon high silicon phase silicate cement with two types of particle size distribution, 20 to 25 parts by weight of fly ash, 20 to 25 parts by weight of building recycled micro powder, and 0.1 to 1 part by weight of powder composite strengthener.

[0026] Preferably, the grinding aid comprises diethanol monoisopropanolamine and triisopropanolamine, and the mass ratio of diethanol monoisopropanolamine to triisopropanolamine is (3-5):(2-4);

[0027] The high silicon iron-rich phase low carbon corrosion-resistant cement binary material is added to a ball mill, and then a grinding aid is added, wherein the amount of the grinding aid added is 0.05-0.06% of the mass of the high silicon iron-rich phase low carbon corrosion-resistant cement binary material;

[0028] In the step of adding the low carbon high silicon phase silicate cement binary material into a ball mill and then adding a grinding aid, the amount of the grinding aid added is 0.05-0.06% of the mass of the low carbon high silicon phase silicate cement binary material.

[0029] Preferably, the mass ratio of high silicon iron-rich phase low carbon corrosion resistant cement with a particle size of 15 to 30 μm to high silicon iron-rich phase low carbon corrosion resistant cement with a particle size of 30 to 50 μm is (4 to 5): (5 to 6);

[0030] The mass ratio of low carbon high silicon phase silicate cement with a particle size of 4 to 15 μm to low carbon high silicon phase silicate cement with a particle size of 15 to 30 μm is (8 to 10):(2 to 4).

[0031] The low-carbon corrosion-resistant composite cement and the preparation method thereof of the present invention have the following beneficial effects compared with the prior art:

[0032] 1. The present invention is based on the "Fuller distribution" gradation design model and the hydration characteristics and grindability of different mineral compositions in each clinker. By adding high-performance grinding aids and designing the ball milling time to control the particle size distribution of the cementitious material, the silicon phase mineral composition in the low-carbon high-silicon phase silicate cement clinker is distributed in a finer particle size range, while the iron-aluminum phase mineral composition in the high-silicon iron-rich phase low-carbon corrosion-resistant cement clinker is distributed in a coarser particle size range, thereby allowing the hydration range of the silicon phase mineral composition in the low-carbon high-silicon phase silicate cement clinker to match the hydration range of the iron-aluminum phase mineral composition in the high-silicon iron-rich phase low-carbon corrosion-resistant cement clinker to the greatest extent, promoting more aluminum ions to enter the gel, improving the polymerization degree and stability of the gel, and optimizing the mechanical properties and corrosion resistance of the gel. At the same time, the present invention uses high-performance grinding aids to greatly shorten the ball milling time of cement clinker and reduce carbon emissions during cement clinker processing.

[0033] 2. The present invention selects high silicon iron-rich phase low carbon corrosion-resistant cement clinker and low carbon high silicon phase silicate cement clinker for compounding. Compatible with C3A and Achieve the effect of synergistic hydration, avoid concentrated distribution of calcium sulfonite, and achieve the effect of uniform enhancement. The present invention replaces the low-carbon, high-silicon phase silicate cement clinker calcined at high temperature with the high-silicon, iron-rich phase, low-carbon, corrosion-resistant cement clinker calcined at low temperature. At the same time, based on the "Fuller distribution" gradation design model, ultrafine fly ash and building recycled micropowder are selected as ultrafine auxiliary cementitious materials and coarser auxiliary cementitious materials, and the particle size distribution of the composite cement is optimized to achieve the effect of close stacking. On the basis of ensuring the performance of the cementitious materials in all aspects, the amount of cement clinker is reduced to the greatest extent, and the carbon emissions in the cement preparation process are reduced, so as to achieve the effect of energy conservation and emission reduction. The present invention forms a synergistic excitation effect with the cement clinker hydration product by adding a composite strengthener, thereby improving the volcanic ash reaction of auxiliary cementitious materials such as fly ash and building recycled micropowder, optimizing the gel structure, and further ensuring the overall mechanical and corrosion resistance of the cementitious materials. DETAILED DESCRIPTION

[0034] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] It should be noted that the order of description of the following embodiments is not intended to limit the preferred order of the embodiments. In addition, in the description of the present application, the term "including" means "including but not limited to". Various embodiments of the present invention may be in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity and should not be understood as a rigid limitation on the scope of the present invention; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the numbered ranges, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated in this article, it is meant to include any cited numbers (fractions or integers) within the indicated range.

[0036] The embodiment of the present application provides a low-carbon, corrosion-resistant composite cement, comprising the following raw materials in parts by weight: 20 to 25 parts of low-carbon, high-silicon phase silicate cement clinker, 30 to 35 parts of high-silicon, iron-rich phase low-carbon, corrosion-resistant cement clinker, 20 to 25 parts of fly ash, 20 to 25 parts of building recycled micropowder, 0 to 5 parts of desulfurized gypsum, and 0.1 to 1 part of powder composite strengthener.

[0037] The composite cement of the present invention adopts the concept of "Fuller distribution" grading design to prepare low-carbon, corrosion-resistant, low-clinker-dosage high-performance composite cement. On the one hand, based on the hydration characteristics and grindability of iron-aluminum phase minerals and silicon phase minerals in the clinker, the particle size distribution of different types of cement clinkers is regulated by adding high-performance grinding aids and designing the ball milling time, so that the silicon phase minerals and the iron-aluminum phase minerals are more matched to form a gel with higher polymerization degree and more stable structure; on the other hand, ultrafine fly ash and building recycled micropowder are selected as ultrafine auxiliary cementitious materials and coarser auxiliary cementitious materials to achieve a close stacking effect. At the same time, the composite strengthener and the cement clinker hydration products form a synergistic excitation effect to improve the hydration degree of auxiliary cementitious materials such as ultrafine fly ash and building recycled micropowder, optimize the gel structure, and thus improve the overall mechanical and corrosion resistance.

[0038] In some embodiments, the low carbon, high silicon phase silicate cement clinker includes the following mineral components in mass fractions: tricalcium silicate (C3S) 70-80%, dicalcium silicate (C2S) 5-10%, tetracalcium aluminoferrite (C4AF) 5-10%, and tricalcium aluminate (C3A) 10-20%.

[0039] In some embodiments, the high silicon iron-rich phase low carbon corrosion-resistant cement clinker includes the following mineral components by mass fraction: calcium sulfosilicate ( Ca5(SiO4)2SO4)25~30%, calcium sulphoaluminate 40-45%, tetracalcium aluminoferrite (C4AF) 20-25%, dicalcium silicate (C2S) 5-10%.

[0040] In some embodiments, the powder composite enhancer includes the following components by mass fraction: 50-65% sodium-based desulfurization ash, 30-45% aluminum sulfate, and 5-15% sodium tripolyphosphate. The aluminum sulfate and sodium tripolyphosphate used are commercially available materials; wherein the sodium-based desulfurization ash includes the components by mass fraction shown in Table 1.

[0041] Table 1-Chemical composition of sodium-based desulfurization ash

[0042]

[0043] In some embodiments, the fly ash includes at least one of ultrafine fly ash, primary fly ash, and secondary fly ash.

[0044] In some embodiments, the particle size of the fly ash is less than or equal to 4 μm.

[0045] In some embodiments, the particle size of the recycled building powder is 50 to 90 μm. The recycled building powder comes from waste C50 concrete, and its main components are cement stone fine powder and limestone powder, and its particle size range is controlled to be 50 to 90 μm. Its chemical composition is shown in Table 2:

[0046] Table 2-Chemical composition of building recycled micro powder

[0047]

[0048] In some embodiments, desulfurized gypsum is a byproduct of the dry desulfurization process in a steel plant, and is mainly composed of calcium sulfite hemihydrate, calcium carbonate, fly ash and calcium hydroxide. Its main chemical components are shown in Table 3:

[0049] Table 3-Chemical composition of desulfurized gypsum

[0050]

[0051]

[0052] The present invention adopts phase and Composite high silicon iron-rich low carbon corrosion resistant cement clinker (25% to 30% Minerals, 40% to 45% Minerals, 20% to 25% C4AF minerals, 5% to 10% C2S) are compounded with high silicon iron-rich low carbon corrosion resistant cement clinker (70% to 80% C3S minerals, 5% to 10% C2S minerals, 5% to 10% C4AF minerals, 10% to 20% C3A content). With aluminum phase (C3A and )'s synergistic hydration reaction optimizes the distribution effect of calcium sulfonite, thereby enhancing the structure of the composite cementitious material and optimizing the strength and toughness of the cementitious slurry; in the pretreatment process of ordinary silicate and high-silicon iron-rich phase low-carbon corrosion-resistant cement clinker, the present invention makes the main distribution intervals of different cement clinkers concentrate in the corresponding intervals of the grading model according to the raw material characteristics to achieve a close stacking effect, and at the same time makes the hydration intervals of silicon phase minerals and aluminum phase minerals match, promotes more aluminum ions to enter the gel, optimizes the gel structure, reduces the amount of clinker, and improves the overall mechanical properties and durability of the material. The present invention also improves the hydration degree of auxiliary cementitious materials and optimizes the pore structure through the synergistic excitation effect between the composite strengthener and the cement hydration product, further matches the hydration intervals of silicon phase minerals and aluminum phase minerals, reduces the amount of cement clinker, and increases the amount of auxiliary cementitious materials such as building recycled micropowder, further achieving the effect of carbon reduction and emission reduction.

[0053] The present invention adopts phase and Low-carbon corrosion-resistant composite cement (25%-30% Minerals, 40%-45% Minerals, 20%-25% C4AF minerals, 5%-10% C2S), use With C3A and The synergistic hydration effect can achieve the effect of uniform distribution of ettringite, optimize the gel structure, reduce the amount of clinker, and improve the overall mechanical properties and durability of the material; at the same time, The mineral phase hydration forms expansive hydration products such as calcium sulfoxide to compensate for the shrinkage of C80 concrete, which can improve the crack resistance of concrete. In addition, the calcination temperature of the high-silicon iron-rich phase low-carbon corrosion-resistant cement clinker is low, which is about 200°C lower than the calcination temperature of traditional silicate cement clinker (1400°C). The coal consumption is significantly reduced, and the carbon emissions are further reduced, realizing the low-carbon preparation of corrosion-resistant, low-clinker dosage, high-performance composite cement.

[0054] Specific phase and The preparation method of the composite high-silicon iron-rich phase low-carbon corrosion-resistant cement clinker is as follows:

[0055] Mix four kinds of raw materials, limestone (60%-70%), phosphogypsum (10%-15%), alumina (20%-25%), and fly ash (5%-10%), and add 0.5% fluorine to ensure and The phases coexist, are mixed and pressed into a cake, and then heated to 1200℃ at 5℃ / min for calcination; after keeping the temperature for 40-45min, the mixture is quickly taken out and blast-cooled to room temperature to prepare calcium sulfosilicate-calcium sulfoaluminate clinker, the main mineral composition of the clinker is 25%-30% Minerals, 40%-45% Minerals, 20%-25% C4AF minerals, 5%-10% C2S.

[0056] The specific preparation method of low carbon high silicon phase silicate cement clinker is:

[0057] Limestone (70%-80%), clay (5%-10%), coal gangue (5%-10%), fly ash (5%-10%) and iron powder (1%-5%) are uniformly mixed, and CuO and CaF2 accounting for 1% of the raw material are used as calcination accelerators, and the temperature is raised to 1450°C at 5°C / min for calcination. After being kept at 1450°C for 30 minutes, the mixture is quickly taken out and blast-cooled to room temperature to produce high C3S silicate cement clinker whose main mineral composition is 70%-80% of C3S minerals, 5%-10% of C2S minerals, 5%-10% of C4AF minerals, and 10%-20% of C3A content ≥75%.

[0058] The low-carbon, corrosion-resistant, low-clinker dosage, high-performance composite cement prepared by the present invention has the characteristics of early strength, corrosion resistance, and shrinkage compensation, which effectively solves the problems of low early strength and poor corrosion resistance of current low-carbon composite cement materials. The high-silicon, iron-rich phase low-carbon, corrosion-resistant cement clinker used can improve the early strength and corrosion resistance of cementitious materials, reduce the steaming time of large-volume prefabricated components, ensure long-term performance, and further reduce overall carbon emissions; the present application incorporates a powder composite strengthener (50% to 65% sodium-based desulfurization ash, 30% to 45% aluminum sulfate, and 5% to 15% sodium tripolyphosphate), and the hydration degree of fly ash and building recycled micropowder is improved through the synergistic effect between sodium-based desulfurization ash and cement clinker hydration products such as calcium hydroxide, thereby optimizing the cementitious material. The pore structure and mechanical properties of the material are improved, thereby further reducing the amount of cement clinker. At the same time, aluminum sulfate and sodium tripolyphosphate are used to regulate the clinker setting time and the morphology of calcium sulfate, optimize the gel microstructure, and achieve the effect of controllable setting time, which has an important guiding role in the research and development and preparation of cementitious materials. The low-carbon, corrosion-resistant, low-clinker-dosage high-performance composite cement prepared by the present invention has a 1d compressive strength of ≥32.6MPa, a 28d compressive strength of ≥58.4Mpa, and a 28d chloride ion diffusion coefficient of 0.54×10 -12 m 2 / s, 180d seawater corrosion resistance coefficient K 180 ≥1.10, and at the same time has stronger ability to resist deformation, and has important practical application value.

[0059] The low-carbon corrosion-resistant composite cement prepared by the present invention uses high-silicon iron-rich phase low-carbon corrosion-resistant cement clinker, which can reduce the calcination temperature to 1200°C, while reducing grinding energy consumption and reducing CO2 emissions in the production process by about 20%. At the same time, the present invention replaces cement clinker with fly ash microbeads, building recycled micropowder, desulfurized gypsum and other admixtures in large amounts, further greatly reducing carbon emissions and achieving the effect of energy saving and emission reduction.

[0060] Based on the same inventive concept, the present invention also provides a method for preparing a low-carbon corrosion-resistant composite cement, comprising the following steps:

[0061] The present invention also provides a method for preparing the low-carbon corrosion-resistant composite cement, comprising the following steps:

[0062] S1. crushing 30 to 35 parts by weight of high-silicon iron-rich phase low-carbon corrosion-resistant cement clinker to a particle size of less than 15 mm to obtain high-silicon iron-rich phase low-carbon corrosion-resistant cement clinker slag;

[0063] S2, crushing 20 to 25 parts by weight of low-carbon high-silicon phase silicate cement clinker to a particle size of less than 15 mm to obtain low-carbon high-silicon phase silicate cement clinker slag;

[0064] S3, mixing high silicon iron-rich phase low carbon corrosion-resistant cement clinker slag with 0 to 3 parts by weight of desulfurized gypsum to obtain high silicon iron-rich phase low carbon corrosion-resistant cement binary material;

[0065] S4, mixing low-carbon high-silicon phase silicate cement clinker slag with 0-2 parts by weight of desulfurized gypsum to obtain low-carbon high-silicon phase silicate cement binary material;

[0066] S5, adding high silicon iron-rich phase low carbon corrosion-resistant cement binary material into a ball mill, adding a grinding aid, and ball milling to obtain a first cement mixture with a particle size of less than 0.05 mm;

[0067] S6, adding a low-carbon high-silicon phase silicate cement binary material into a ball mill, and then adding a grinding aid, and ball milling to obtain a second cement mixture with a particle size of less than 0.03 mm;

[0068] S7, classifying the first cement mixture through an air flow classifier to obtain high-silicon iron-rich phase low-carbon corrosion-resistant cement with two particle size distributions of 15 to 30 μm and 30 to 50 μm;

[0069] S8, classifying the second cement mixture through an air flow classifier to obtain low-carbon high-silicon phase silicate cement with two particle size distributions of 4 to 15 μm and 15 to 30 μm;

[0070] S9. Mix two types of high-silicon iron-rich phase low-carbon corrosion-resistant cement with particle size distribution, two types of low-carbon high-silicon phase silicate cement with particle size distribution, 20 to 25 parts by weight of fly ash, 20 to 25 parts by weight of building recycled micropowder, and 0.1 to 1 part by weight of powder composite strengthener to obtain low-carbon corrosion-resistant composite cement.

[0071] In some embodiments, the grinding aid includes diethanol monoisopropanolamine and triisopropanolamine, and the mass ratio of diethanol monoisopropanolamine to triisopropanolamine is (3-5):(2-4).

[0072] In some embodiments, high silicon iron-rich phase low carbon corrosion resistant cement binary material is added to a ball mill, and then a grinding aid is added, and the amount of the grinding aid added is 0.05-0.06% of the mass of the high silicon iron-rich phase low carbon corrosion resistant cement binary material.

[0073] In some embodiments, in the step of adding low carbon high silicon phase silicate cement binary material into a ball mill and then adding a grinding aid, the amount of the grinding aid added is 0.05-0.06% of the mass of the low carbon high silicon phase silicate cement binary material.

[0074] In some embodiments, the mass ratio of high silicon iron-rich phase low carbon corrosion resistant cement with a particle size of 15 to 30 μm to high silicon iron-rich phase low carbon corrosion resistant cement with a particle size of 30 to 50 μm is (4 to 5): (5 to 6).

[0075] In some embodiments, the mass ratio of low carbon high silicon phase silicate cement with a particle size of 4 to 15 μm to low carbon high silicon phase silicate cement with a particle size of 15 to 30 μm is (8 to 10):(2 to 4).

[0076] In some embodiments, the air flow classifier speed is controlled to be 100-200 rpm, and the first cement mixture is classified by the air flow classifier to obtain high-silicon iron-rich phase low-carbon corrosion-resistant cement with two particle size distributions of 15-30 μm and 30-50 μm;

[0077] In some embodiments, the air flow classifier speed is controlled to be 500-1000 rpm, and the second cement mixture is classified by the air flow classifier to obtain low carbon high silicon phase silicate cement with two particle size distributions of 4-15 μm and 15-30 μm.

[0078] The present invention adopts phase and Composite high silicon iron-rich low carbon corrosion resistant cement clinker (25% to 30% Minerals, 40% to 45% Minerals, 20% to 25% C4AF minerals, 5% to 10% C2S) are compounded with low-carbon high-silicon phase silicate cement clinker. Compatible with C3A and The synergistic hydration effect can achieve the effect of uniform distribution of calcium sulfonite, optimize the gel structure, reduce the amount of clinker, and improve the overall mechanical properties and durability of the material. Based on the hydration characteristics and grindability of iron-aluminum phase minerals and silicon phase minerals in the clinker, the particle size distribution range of the cementitious material is adjusted by adding high-performance grinding aids and designing the ball milling time. The main particle size range of high-silicon iron-rich phase low-carbon corrosion-resistant cement clinker is controlled within 15-30μm and 30-50μm by combining the air flow classifier, and the main particle size range of low-carbon high-silicon phase silicate cement clinker is controlled within 4-15μm and 15-30μm, so that the hydration range of silicon phase minerals and aluminum phase minerals is matched, which promotes more aluminum ions to enter the gel and improves the polymerization degree and stability of the gel. In addition, fly ash and building recycled micro powder are selected as ultrafine auxiliary cementitious materials and coarse auxiliary cementitious materials to achieve the effect of tight stacking. During the preparation process, the graded cement clinker, fly ash, building recycled micro powder, gypsum and powder composite strengthener are added into a dry mixer at the same time and stirred for 10 minutes to obtain the carbon corrosion-resistant low clinker dosage high-performance composite cement.

[0079] The low-carbon corrosion-resistant composite cement and its preparation method of the present invention are further described below with specific examples. This section further illustrates the content of the present invention in conjunction with specific examples, but should not be construed as limiting the present invention. Unless otherwise specified, the technical means used in the examples are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0080] In the following embodiments and comparative examples, fly ash is produced by a chemical reagent company in Tianjin, with an average particle size of 2 μm; building recycled micropowder is provided by Suzhou Lvpu New Material Technology Co., Ltd., with an average particle size of 70 μm, including the following components by mass fraction: SiO2 25.26%, Al2O3 5.27%, Fe2O3 2.02%, CaO 30.81%, SO3 1.35%, K2O0.14%, MgO 0.43%, Na2O 0.413%, LOI 33.947%; desulfurized gypsum is produced by Jiangsu Yonggang Group, including the following components by mass fraction: SiO2 2.6%, Al2O3 0.7%, Fe2O30.82%, CaO 43.31%, SO3 40.73%, K2O0.14%, MgO 0.91%, LOI 3.36%; aluminum sulfate and sodium tripolyphosphate are commercially available materials provided by Henan Boyue Chemical Products Co., Ltd.; diethanol monoisopropanolamine and triisopropanolamine (content ≥ 99.0%) are provided by Shanghai Xiangu Chemical Co., Ltd.;

[0081] The low carbon high silicon phase silicate cement clinker includes the following mineral components by mass fraction: tricalcium silicate (C3S) 75%, dicalcium silicate (C2S) 8%, tetracalcium aluminoferrite (C4AF) 7%, tricalcium aluminate (C3A) 10%;

[0082] High silicon iron-rich phase low carbon corrosion-resistant cement clinker includes the following mineral components by mass fraction: calcium sulfosilicate ( Ca5(SiO4)2SO4)25%, calcium sulphoaluminate 40%, tetracalcium aluminoferrate (C4AF) 25%, dicalcium silicate (C2S) 10%;

[0083] The powder composite enhancer includes the following components by mass fraction: 50% sodium-based desulfurization ash, 40% aluminum sulfate, and 10% sodium tripolyphosphate; the sodium-based desulfurization ash includes the following components by mass fraction: SiO2 0.24%, Al2O3 0.011%, Fe2O3 0.037%, CaO 0.332%, SO3 51.89%, K2O 0.006%, MgO 0.43%, Na2O 43.91%, and LOI 3.36%;

[0084] The grinding aids include diethanol monoisopropanolamine and triisopropanolamine, and the mass ratio of diethanol monoisopropanolamine to triisopropanolamine is 3:2.

[0085] Example 1

[0086] The embodiment of the present application provides a low-carbon corrosion-resistant composite cement, comprising the following raw materials in parts by weight: 25 parts of low-carbon high-silicon phase silicate cement clinker, 32 parts of high-silicon iron-rich phase low-carbon corrosion-resistant cement clinker, 25 parts of fly ash, 20 parts of building recycled micro powder, 4 parts of desulfurized gypsum, and 0.5 parts of powder composite strengthener;

[0087] The preparation method of the low-carbon corrosion-resistant composite cement comprises the following steps:

[0088] S1. crushing 32 parts by weight of high-silicon iron-rich phase low-carbon corrosion-resistant cement clinker to a particle size of less than 15 mm to obtain high-silicon iron-rich phase low-carbon corrosion-resistant cement clinker slag;

[0089] S2, crushing 25 parts by weight of low-carbon high-silicon phase silicate cement clinker to a particle size of less than 15 mm to obtain low-carbon high-silicon phase silicate cement clinker slag;

[0090] S3, mixing high silicon iron-rich phase low carbon corrosion-resistant cement clinker slag with 2 parts by weight of desulfurized gypsum to obtain high silicon iron-rich phase low carbon corrosion-resistant cement binary material;

[0091] S4, mixing low-carbon high-silicon phase silicate cement clinker slag with 2 parts by weight of desulfurized gypsum to obtain a low-carbon high-silicon phase silicate cement binary material;

[0092] S5, adding high silicon iron-rich phase low carbon corrosion-resistant cement binary material into a ball mill, adding a grinding aid, and ball milling to obtain a first cement mixture with a particle size of less than 0.05 mm;

[0093] S6, adding a low-carbon high-silicon phase silicate cement binary material into a ball mill, and then adding a grinding aid, and ball milling to obtain a second cement mixture with a particle size of less than 0.03 mm;

[0094] S7, classifying the first cement mixture through an air flow classifier to obtain high-silicon iron-rich phase low-carbon corrosion-resistant cement with two particle size distributions of 15 to 30 μm and 30 to 50 μm;

[0095] S8, classifying the second cement mixture through an air flow classifier to obtain low-carbon high-silicon phase silicate cement with two particle size distributions of 4 to 15 μm and 15 to 30 μm;

[0096] S9, mixing two kinds of high silicon iron-rich phase low carbon corrosion resistant cement with particle size distribution, two kinds of low carbon high silicon phase silicate cement with particle size distribution, 25 parts by weight of fly ash, 20 parts by weight of building recycled micro powder, and 0.5 parts by weight of powder composite strengthener, and stirring for 10 minutes to obtain low carbon corrosion resistant composite cement;

[0097] Among them, in the step of adding high silicon iron-rich phase low carbon corrosion-resistant cement binary material into a ball mill and then adding a grinding aid, the amount of the grinding aid added is 0.05% of the mass of the high silicon iron-rich phase low carbon corrosion-resistant cement binary material;

[0098] In the step of adding low carbon high silicon phase silicate cement binary material into a ball mill, and then adding a grinding aid, the amount of the grinding aid added is 0.05% of the mass of the low carbon high silicon phase silicate cement binary material;

[0099] The mass ratio of high silicon iron-rich phase low carbon corrosion resistant cement with a particle size of 15 to 30 μm to high silicon iron-rich phase low carbon corrosion resistant cement with a particle size of 30 to 50 μm is 4:5;

[0100] The mass ratio of low carbon high silicon phase silicate cement with a particle size of 4 to 15 μm to low carbon high silicon phase silicate cement with a particle size of 15 to 30 μm is 8:2.

[0101] Example 2

[0102] The embodiment of the present application provides a low-carbon, corrosion-resistant composite cement, comprising the following raw materials in parts by weight: 25 parts of low-carbon, high-silicon phase silicate cement clinker, 32 parts of high-silicon, iron-rich phase low-carbon, corrosion-resistant cement clinker, 25 parts of fly ash, 20 parts of building recycled micropowder, 4 parts of desulfurized gypsum, and 0.1 parts of powder composite strengthener.

[0103] The preparation method of the low-carbon corrosion-resistant composite cement comprises the following steps:

[0104] S1. crushing 32 parts by weight of high-silicon iron-rich phase low-carbon corrosion-resistant cement clinker to a particle size of less than 15 mm to obtain high-silicon iron-rich phase low-carbon corrosion-resistant cement clinker slag;

[0105] S2, crushing 25 parts by weight of low-carbon high-silicon phase silicate cement clinker to a particle size of less than 15 mm to obtain low-carbon high-silicon phase silicate cement clinker slag;

[0106] S3, mixing high silicon iron-rich phase low carbon corrosion-resistant cement clinker slag with 2 parts by weight of desulfurized gypsum to obtain high silicon iron-rich phase low carbon corrosion-resistant cement binary material;

[0107] S4, mixing low-carbon high-silicon phase silicate cement clinker slag with 2 parts by weight of desulfurized gypsum to obtain a low-carbon high-silicon phase silicate cement binary material;

[0108] S5, adding high silicon iron-rich phase low carbon corrosion-resistant cement binary material into a ball mill, adding a grinding aid, and ball milling to obtain a first cement mixture with a particle size of less than 0.05 mm;

[0109] S6, adding a low-carbon high-silicon phase silicate cement binary material into a ball mill, and then adding a grinding aid, and ball milling to obtain a second cement mixture with a particle size of less than 0.03 mm;

[0110] S7, classifying the first cement mixture through an air flow classifier to obtain high-silicon iron-rich phase low-carbon corrosion-resistant cement with two particle size distributions of 15 to 30 μm and 30 to 50 μm;

[0111] S8, classifying the second cement mixture through an air flow classifier to obtain low-carbon high-silicon phase silicate cement with two particle size distributions of 4 to 15 μm and 15 to 30 μm;

[0112] S9, mixing two kinds of high silicon iron-rich phase low carbon corrosion resistant cement with particle size distribution, two kinds of low carbon high silicon phase silicate cement with particle size distribution, 25 parts by weight of fly ash, 20 parts by weight of building recycled micro powder, and 0.1 parts by weight of powder composite strengthener, and stirring for 10 minutes to obtain low carbon corrosion resistant composite cement;

[0113] Among them, in the step of adding high silicon iron-rich phase low carbon corrosion-resistant cement binary material into a ball mill and then adding a grinding aid, the amount of the grinding aid added is 0.05% of the mass of the high silicon iron-rich phase low carbon corrosion-resistant cement binary material;

[0114] In the step of adding low carbon high silicon phase silicate cement binary material into a ball mill, and then adding a grinding aid, the amount of the grinding aid added is 0.05% of the mass of the low carbon high silicon phase silicate cement binary material;

[0115] The mass ratio of high silicon iron-rich phase low carbon corrosion resistant cement with a particle size of 15 to 30 μm to high silicon iron-rich phase low carbon corrosion resistant cement with a particle size of 30 to 50 μm is 4:5;

[0116] The mass ratio of low carbon high silicon phase silicate cement with a particle size of 4 to 15 μm to low carbon high silicon phase silicate cement with a particle size of 15 to 30 μm is 8:2.

[0117] Example 3

[0118] The embodiment of the present application provides a low-carbon corrosion-resistant composite cement, comprising the following raw materials in parts by weight: 25 parts of low-carbon high-silicon phase silicate cement clinker, 32 parts of high-silicon iron-rich phase low-carbon corrosion-resistant cement clinker, 25 parts of fly ash, 20 parts of building recycled micro powder, 0 parts of desulfurized gypsum, and 0.5 parts of powder composite strengthener;

[0119] The preparation method of the low-carbon corrosion-resistant composite cement comprises the following steps:

[0120] S1. crushing 32 parts by weight of high-silicon iron-rich phase low-carbon corrosion-resistant cement clinker to a particle size of less than 15 mm to obtain high-silicon iron-rich phase low-carbon corrosion-resistant cement clinker slag;

[0121] S2, crushing 25 parts by weight of low-carbon high-silicon phase silicate cement clinker to a particle size of less than 15 mm to obtain low-carbon high-silicon phase silicate cement clinker slag;

[0122] S3, mixing high silicon iron-rich phase low carbon corrosion-resistant cement clinker slag with 0 weight parts of desulfurized gypsum to obtain high silicon iron-rich phase low carbon corrosion-resistant cement binary material;

[0123] S4, mixing low-carbon high-silicon phase silicate cement clinker slag with 0 parts by weight of desulfurized gypsum to obtain a low-carbon high-silicon phase silicate cement binary material;

[0124] S5, adding high silicon iron-rich phase low carbon corrosion-resistant cement binary material into a ball mill, adding a grinding aid, and ball milling to obtain a first cement mixture with a particle size of less than 0.05 mm;

[0125] S6, adding a low-carbon high-silicon phase silicate cement binary material into a ball mill, and then adding a grinding aid, and ball milling to obtain a second cement mixture with a particle size of less than 0.03 mm;

[0126] S7, classifying the first cement mixture through an air flow classifier to obtain high-silicon iron-rich phase low-carbon corrosion-resistant cement with two particle size distributions of 15 to 30 μm and 30 to 50 μm;

[0127] S8, classifying the second cement mixture through an air flow classifier to obtain low-carbon high-silicon phase silicate cement with two particle size distributions of 4 to 15 μm and 15 to 30 μm;

[0128] S9, mixing two kinds of high silicon iron-rich phase low carbon corrosion resistant cement with particle size distribution, two kinds of low carbon high silicon phase silicate cement with particle size distribution, 25 parts by weight of fly ash, 20 parts by weight of building recycled micro powder, and 0.5 parts by weight of powder composite strengthener, and stirring for 10 minutes to obtain low carbon corrosion resistant composite cement;

[0129] Among them, in the step of adding high silicon iron-rich phase low carbon corrosion-resistant cement binary material into a ball mill and then adding a grinding aid, the amount of the grinding aid added is 0.05% of the mass of the high silicon iron-rich phase low carbon corrosion-resistant cement binary material;

[0130] In the step of adding low carbon high silicon phase silicate cement binary material into a ball mill, and then adding a grinding aid, the amount of the grinding aid added is 0.05% of the mass of the low carbon high silicon phase silicate cement binary material;

[0131] The mass ratio of high silicon iron-rich phase low carbon corrosion resistant cement with a particle size of 15 to 30 μm to high silicon iron-rich phase low carbon corrosion resistant cement with a particle size of 30 to 50 μm is 4:5;

[0132] The mass ratio of low carbon high silicon phase silicate cement with a particle size of 4 to 15 μm to low carbon high silicon phase silicate cement with a particle size of 15 to 30 μm is 8:2.

[0133] Example 4

[0134] The embodiment of the present application provides a low-carbon corrosion-resistant composite cement, comprising the following raw materials in parts by weight: 25 parts of low-carbon high-silicon phase silicate cement clinker, 32 parts of high-silicon iron-rich phase low-carbon corrosion-resistant cement clinker, 20 parts of fly ash, 25 parts of building recycled micro powder, 4 parts of desulfurized gypsum, and 0.5 parts of powder composite strengthener;

[0135] The preparation method of the low-carbon corrosion-resistant composite cement comprises the following steps:

[0136] S1. crushing 32 parts by weight of high-silicon iron-rich phase low-carbon corrosion-resistant cement clinker to a particle size of less than 15 mm to obtain high-silicon iron-rich phase low-carbon corrosion-resistant cement clinker slag;

[0137] S2, crushing 25 parts by weight of low-carbon high-silicon phase silicate cement clinker to a particle size of less than 15 mm to obtain low-carbon high-silicon phase silicate cement clinker slag;

[0138] S3, mixing high silicon iron-rich phase low carbon corrosion-resistant cement clinker slag with 2 parts by weight of desulfurized gypsum to obtain high silicon iron-rich phase low carbon corrosion-resistant cement binary material;

[0139] S4, mixing low-carbon high-silicon phase silicate cement clinker slag with 2 parts by weight of desulfurized gypsum to obtain a low-carbon high-silicon phase silicate cement binary material;

[0140] S5, adding high silicon iron-rich phase low carbon corrosion-resistant cement binary material into a ball mill, adding a grinding aid, and ball milling to obtain a first cement mixture with a particle size of less than 0.05 mm;

[0141] S6, adding a low-carbon high-silicon phase silicate cement binary material into a ball mill, and then adding a grinding aid, and ball milling to obtain a second cement mixture with a particle size of less than 0.03 mm;

[0142] S7, classifying the first cement mixture through an air flow classifier to obtain high-silicon iron-rich phase low-carbon corrosion-resistant cement with two particle size distributions of 15 to 30 μm and 30 to 50 μm;

[0143] S8, classifying the second cement mixture through an air flow classifier to obtain low-carbon high-silicon phase silicate cement with two particle size distributions of 4 to 15 μm and 15 to 30 μm;

[0144] S9, mixing two kinds of high silicon iron-rich phase low carbon corrosion resistant cement with particle size distribution, two kinds of low carbon high silicon phase silicate cement with particle size distribution, 20 parts by weight of fly ash, 25 parts by weight of building recycled micro powder, and 0.5 parts by weight of powder composite strengthener, and stirring for 10 minutes to obtain low carbon corrosion resistant composite cement;

[0145] Among them, in the step of adding high silicon iron-rich phase low carbon corrosion-resistant cement binary material into a ball mill and then adding a grinding aid, the amount of the grinding aid added is 0.05% of the mass of the high silicon iron-rich phase low carbon corrosion-resistant cement binary material;

[0146] In the step of adding low carbon high silicon phase silicate cement binary material into a ball mill, and then adding a grinding aid, the amount of the grinding aid added is 0.05% of the mass of the low carbon high silicon phase silicate cement binary material;

[0147] The mass ratio of high silicon iron-rich phase low carbon corrosion resistant cement with a particle size of 15 to 30 μm to high silicon iron-rich phase low carbon corrosion resistant cement with a particle size of 30 to 50 μm is 4:5;

[0148] The mass ratio of low carbon high silicon phase silicate cement with a particle size of 4 to 15 μm to low carbon high silicon phase silicate cement with a particle size of 15 to 30 μm is 8:2.

[0149] Comparative Example 1

[0150] This comparative example provides a composite cement, comprising the following raw materials in parts by weight: 57 parts of low-carbon high-silicon phase silicate cement clinker, 24 parts of fly ash, 19 parts of building recycled micro powder, 4 parts of desulfurized gypsum, and 0.5 parts of powder composite strengthener;

[0151] The preparation method of the above composite cement comprises the following steps:

[0152] S1. crushing 57 parts by weight of low-carbon high-silicon phase silicate cement clinker to a particle size of less than 15 mm to obtain low-carbon high-silicon phase silicate cement clinker slag;

[0153] S2, mixing low-carbon high-silicon phase silicate cement clinker slag with 4 parts by weight of desulfurized gypsum to obtain a low-carbon high-silicon phase silicate cement binary material;

[0154] S3, adding a low-carbon high-silicon phase silicate cement binary material into a ball mill, and then adding a grinding aid, and ball milling to obtain a first cement mixture with a particle size of less than 0.03 mm;

[0155] S4, classifying the first cement mixture through an air flow classifier to obtain low-carbon high-silicon phase silicate cement with two particle size distributions of 4 to 15 μm and 15 to 30 μm;

[0156] S5, mixing two kinds of low-carbon high-silicon phase silicate cement with different particle size distributions, 24 parts by weight of fly ash, 19 parts by weight of building recycled micro powder, and 0.5 parts by weight of powder composite strengthener, and stirring for 10 minutes to obtain composite cement;

[0157] The step of adding the low-carbon high-silicon phase silicate cement binary material into a ball mill and then adding a grinding aid is performed in an amount of 0.05% of the mass of the low-carbon high-silicon phase silicate cement binary material.

[0158] The mass ratio of low carbon high silicon phase silicate cement with a particle size of 4 to 15 μm to low carbon high silicon phase silicate cement with a particle size of 15 to 30 μm is 8:2.

[0159] Comparative Example 2

[0160] This comparative example provides a composite cement, comprising the following raw materials in parts by weight: 57 parts of low-carbon high-silicon phase silicate cement clinker, 43 parts of fly ash, 4 parts of desulfurized gypsum, and 0.5 parts of a powder composite strengthener.

[0161] The preparation method of the above composite cement comprises the following steps:

[0162] S1. crushing 57 parts by weight of low-carbon high-silicon phase silicate cement clinker to a particle size of less than 15 mm to obtain low-carbon high-silicon phase silicate cement clinker slag;

[0163] S2, mixing low-carbon high-silicon phase silicate cement clinker slag with 4 parts by weight of desulfurized gypsum to obtain a low-carbon high-silicon phase silicate cement binary material;

[0164] S3, adding a low-carbon high-silicon phase silicate cement binary material into a ball mill, and then adding a grinding aid, and ball milling to obtain a first cement mixture with a particle size of less than 0.03 mm;

[0165] S4, classifying the first cement mixture through an air flow classifier to obtain low-carbon high-silicon phase silicate cement with two particle size distributions of 4 to 15 μm and 15 to 30 μm;

[0166] S5, mixing two kinds of low-carbon high-silicon phase silicate cement with different particle size distributions, 43 parts by weight of fly ash, 19 parts by weight of building recycled micro powder, and 0.5 parts by weight of powder composite strengthener, and stirring for 10 minutes to obtain composite cement;

[0167] The step of adding the low-carbon high-silicon phase silicate cement binary material into a ball mill and then adding a grinding aid is performed in an amount of 0.05% of the mass of the low-carbon high-silicon phase silicate cement binary material.

[0168] The mass ratio of low carbon high silicon phase silicate cement with a particle size of 4 to 15 μm to low carbon high silicon phase silicate cement with a particle size of 15 to 30 μm is 8:2.

[0169] Comparative Example 3

[0170] This comparative example provides a low-carbon corrosion-resistant composite cement, comprising the following raw materials in parts by weight: 25 parts of low-carbon high-silicon phase silicate cement clinker, 32 parts of high-silicon iron-rich phase low-carbon corrosion-resistant cement clinker, 25 parts of fly ash, 20 parts of building recycled micro powder, 4 parts of desulfurized gypsum, and 0.5 parts of powder composite strengthener;

[0171] The preparation method of the low-carbon corrosion-resistant composite cement comprises the following steps:

[0172] S1. crushing 25 parts by weight of high-silicon iron-rich phase low-carbon corrosion-resistant cement clinker to a particle size of less than 15 mm to obtain high-silicon iron-rich phase low-carbon corrosion-resistant cement clinker slag;

[0173] S2, crushing 32 parts by weight of low-carbon high-silicon phase silicate cement clinker to a particle size of less than 15 mm to obtain low-carbon high-silicon phase silicate cement clinker slag;

[0174] S3, mixing high silicon iron-rich phase low carbon corrosion-resistant cement clinker slag with 2 parts by weight of desulfurized gypsum to obtain high silicon iron-rich phase low carbon corrosion-resistant cement binary material;

[0175] S4, mixing low-carbon high-silicon phase silicate cement clinker slag with 2 parts by weight of desulfurized gypsum to obtain low-carbon high-silicon phase silicate cement binary material;

[0176] S5, adding high silicon iron-rich phase low carbon corrosion-resistant cement binary material into a ball mill, adding a grinding aid, and ball milling to obtain a first cement mixture with a particle size of less than 0.05 mm;

[0177] S6, adding a low-carbon high-silicon phase silicate cement binary material into a ball mill, and then adding a grinding aid, and ball milling to obtain a second cement mixture with a particle size of less than 0.03 mm;

[0178] S7, classifying the first cement mixture through an air flow classifier to obtain high-silicon iron-rich phase low-carbon corrosion-resistant cement with two particle size distributions of 4 to 15 μm and 15 to 30 μm;

[0179] S8, classifying the second cement mixture through an air flow classifier to obtain low-carbon high-silicon phase silicate cement with a particle size of 15 to 30 μm and 30 to 50 μm;

[0180] S9, mixing two kinds of high silicon iron-rich phase low carbon corrosion resistant cement with particle size distribution, two kinds of low carbon high silicon phase silicate cement with particle size distribution, 25 parts by weight of fly ash, 20 parts by weight of building recycled micro powder, and 0.5 parts by weight of powder composite strengthener, and stirring for 10 minutes to obtain low carbon corrosion resistant composite cement;

[0181] Among them, in the step of adding high silicon iron-rich phase low carbon corrosion-resistant cement binary material into a ball mill and then adding a grinding aid, the amount of the grinding aid added is 0.05% of the mass of the high silicon iron-rich phase low carbon corrosion-resistant cement binary material;

[0182] In the step of adding low carbon high silicon phase silicate cement binary material into a ball mill, and then adding a grinding aid, the amount of the grinding aid added is 0.05% of the mass of the low carbon high silicon phase silicate cement binary material;

[0183] The mass ratio of high silicon iron-rich phase low carbon corrosion resistant cement with a particle size of 4 to 15 μm to high silicon iron-rich phase low carbon corrosion resistant cement with a particle size of 15 to 30 μm is 4:5;

[0184] The mass ratio of low carbon high silicon phase silicate cement with a particle size of 15 to 30 μm to low carbon high silicon phase silicate cement with a particle size of 30 to 50 μm is 8:2.

[0185] The low-carbon corrosion-resistant composite cements prepared in Examples 1 to 4 and the composite cements prepared in Comparative Examples 1 to 3 were subjected to compressive strength, chloride ion diffusion tests and seawater erosion resistance tests. The specific operations are as follows:

[0186] Mechanical properties test method: For the specific test method, refer to "Test Method for Strength of Cement Mortar (ISO Method)" (GB / T17671-2021), and the test results are shown in Table 4.

[0187] Chloride ion diffusion test: For the specific test method, refer to "Test of Chloride Ion Diffusion Coefficient of Cement" (JC / T1086-2008). The test results are shown in Table 4.

[0188] Seawater erosion resistance test: For specific experimental methods, refer to "Test Method for Seawater Erosion Resistance of Cement" (GB / T38140-2019), and the test results are shown in Table 4.

[0189] Linear expansion test: The specific experimental method refers to the "Test method for drying shrinkage and cracking performance of cement mortar and concrete" (GB / T 29417-2012). The test results are shown in Table 4.

[0190] The experimental results are shown in the following table:

[0191] Table 4-Composite cement test performance

[0192]

[0193] As can be seen from Table 2, the low-carbon, corrosion-resistant composite cement prepared in the embodiment of the present invention has high 3d and 28d compressive strengths and good mechanical properties; this indicates that in the raw material ratio, while comprehensively considering carbon emissions and corrosion resistance, fly ash and building recycled micropowder are added, and the composite powder is added with a powder composite strengthener for auxiliary stimulation, so that the composite cement obtained has good comprehensive performance. By comparing Comparative Example 3 with Example 1, it can be seen that when the main particle size ranges of high-silicon iron-rich phase low-carbon corrosion-resistant cement clinker and low-carbon high-silicon phase silicate cement clinker are controlled in the ranges of 15-30μm and 30-50μm and 4-15μm and 15-30μm, respectively, the hydration range of iron-aluminum phases such as C4AF in the high-silicon iron-rich phase low-carbon corrosion-resistant cement clinker can be effectively matched with the hydration range of silicon phase minerals such as C3S in the low-carbon high-silicon phase silicate cement clinker, promoting more Al 3+ Enter the CSH gel, thereby optimizing the gel structure, reducing the amount of cement clinker, ensuring cement performance, reducing cement production costs, and improving its corrosion resistance. Compared with the sample without the addition of ferroaluminate cement (Comparative Example 1), the sample in which ferroaluminate cement and ordinary Portland cement are collaboratively graded (Example 1) has better comprehensive performance of the cementitious material. Compared with the sample without the addition of ordinary Portland cement (Comparative Example 2), the sample in which ferroaluminate cement and ordinary Portland cement are collaboratively graded (Example 1) has better later mechanical properties and corrosion resistance. Compared with the sample with only a small amount of powder composite strengthener added (Example 2), the sample with an appropriate amount of powder-based strengthener added (Example 1), not only the early strength, but also the setting time is controlled, while avoiding the aggregation of calcium aluminate, the pore structure is optimized, and the corrosion resistance is stronger.

[0194] It can be understood that the technical features of the above-described embodiments can be arbitrarily combined. In order to make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0195] The above are only preferred embodiments of the present application, and only specifically describe the technical principles of the present application. These descriptions are only for explaining the principles of the present application and cannot be interpreted as limiting the scope of protection of the present application in any way. Based on the explanation here, any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application, and other specific implementation methods of the present application that can be associated with the technicians in this field without creative work, should be included in the scope of protection of the present application.

Claims

1. A low-carbon corrosion-resistant composite cement, characterized in that: The method comprises the following raw materials in parts by weight: 20-25 parts of low-carbon high-silicon phase silicate cement clinker, 30-35 parts of high-silicon iron-rich phase low-carbon corrosion-resistant cement clinker, 20-25 parts of fly ash, 20-25 parts of building recycled micro powder, 0-5 parts of desulfurized gypsum, and 0.1-1 parts of powder composite strengthener.

2. The low-carbon corrosion-resistant composite cement according to claim 1, characterized in that: The low-carbon high-silicon phase silicate cement clinker comprises the following components in mass fractions: 70-80% of tricalcium silicate, 5-10% of dicalcium silicate, 5-10% of tetracalcium aluminoferrite, and 10-20% of tricalcium aluminate.

3. The low-carbon corrosion-resistant composite cement according to claim 1, characterized in that: The high-silicon iron-rich phase low-carbon corrosion-resistant cement clinker comprises the following components in mass fractions: 25-30% of calcium sulfosilicate, 40-45% of calcium sulfoaluminate, 20-25% of tetracalcium aluminoferrite, and 5-10% of dicalcium silicate.

4. The low-carbon corrosion-resistant composite cement according to claim 1, characterized in that: The powder composite enhancer comprises the following components by mass fraction: 50-65% of sodium-based desulfurization ash, 30-45% of aluminum sulfate, and 5-15% of sodium tripolyphosphate; The sodium-based desulfurization ash includes the following components in mass fractions: SiO2 0.24%, Al2O3 0.011%, Fe2O3 0.037%, CaO 0.332%, SO3 51.89%, K2O 0.006%, MgO 0.43%, Na2O 43.91%, and LOI 3.36%.

5. The low-carbon corrosion-resistant composite cement according to claim 1, characterized in that: The fly ash includes at least one of superfine fly ash, primary fly ash and secondary fly ash.

6. The low-carbon corrosion-resistant composite cement according to claim 1, characterized in that: The particle size of the building recycled micro powder is 50 to 90 μm; The building recycled fine powder includes the following components by mass fraction: SiO2 25.26%, Al2O3 5.27%, Fe2O32.02%, CaO 30.81%, SO3 1.35%, K2O 0.14%, MgO 0.43%, Na2O 0.413%, LOI 33.947%; The particle size of the fly ash is less than or equal to 4 μm.

7. The low-carbon corrosion-resistant composite cement according to claim 1, characterized in that: The desulfurized gypsum comprises the following components in mass fractions: SiO2 2.6%, Al2O3 0.7%, Fe2O3 0.82%, CaO 43.31%, SO3 40.73%, K2O 0.14%, MgO 0.91%, and LOI 3.36%.

8. A method for preparing the low-carbon corrosion-resistant composite cement according to any one of claims 1 to 7, characterized in that: The following steps are involved: Crushing 30 to 35 parts by weight of high-silicon iron-rich phase low-carbon corrosion-resistant cement clinker to a particle size of less than 15 mm to obtain high-silicon iron-rich phase low-carbon corrosion-resistant cement clinker slag; crushing 20 to 25 parts by weight of low-carbon high-silicon phase silicate cement clinker to a particle size of less than 15 mm to obtain low-carbon high-silicon phase silicate cement clinker slag; The high-silicon iron-rich phase low-carbon corrosion-resistant cement clinker slag is mixed with 0 to 3 parts by weight of desulfurized gypsum to obtain a high-silicon iron-rich phase low-carbon corrosion-resistant cement binary material; The low-carbon high-silicon phase silicate cement clinker residue is mixed with 0 to 2 parts by weight of desulfurized gypsum to obtain a low-carbon high-silicon phase silicate cement binary material; Adding the high-silicon iron-rich phase low-carbon corrosion-resistant cement binary material into a ball mill, adding a grinding aid, and ball milling to obtain a first cement mixture with a particle size of less than 0.05 mm; Adding the low-carbon high-silicon phase silicate cement binary material into a ball mill, adding a grinding aid, and ball milling to obtain a second cement mixture with a particle size of less than 0.03 mm; The first cement mixture is classified by an air flow classifier to obtain high-silicon iron-rich phase low-carbon corrosion-resistant cement with two particle size distributions of 15 to 30 μm and 30 to 50 μm; The second cement mixture is classified by an air flow classifier to obtain low-carbon high-silicon phase silicate cement with two particle size distributions of 4 to 15 μm and 15 to 30 μm; Low carbon corrosion resistant composite cement is obtained by mixing two types of high silicon iron-rich phase low carbon corrosion resistant cement with two types of particle size distribution, two types of low carbon high silicon phase silicate cement with two types of particle size distribution, 20 to 25 parts by weight of fly ash, 20 to 25 parts by weight of building recycled micro powder, and 0.1 to 1 part by weight of powder composite strengthener.

9. The method for preparing low-carbon corrosion-resistant composite cement according to claim 8, characterized in that: The grinding aid comprises diethanol monoisopropanolamine and triisopropanolamine, and the mass ratio of the diethanol monoisopropanolamine to the triisopropanolamine is (3-5):(2-4); The high silicon iron-rich phase low carbon corrosion-resistant cement binary material is added to a ball mill, and then a grinding aid is added, wherein the amount of the grinding aid added is 0.05-0.06% of the mass of the high silicon iron-rich phase low carbon corrosion-resistant cement binary material; In the step of adding the low carbon high silicon phase silicate cement binary material into a ball mill and then adding a grinding aid, the amount of the grinding aid added is 0.05-0.06% of the mass of the low carbon high silicon phase silicate cement binary material.

10. The method for preparing low-carbon corrosion-resistant composite cement according to claim 8, characterized in that: The mass ratio of high silicon iron-rich phase low carbon corrosion resistant cement with a particle size of 15 to 30 μm to high silicon iron-rich phase low carbon corrosion resistant cement with a particle size of 30 to 50 μm is (4 to 5): (5 to 6); The mass ratio of low carbon high silicon phase silicate cement with a particle size of 4 to 15 μm to low carbon high silicon phase silicate cement with a particle size of 15 to 30 μm is (8 to 10):(2 to 4).

Citation Information

Patent Citations

  • Quick-setting quick-hardening high-strength low-carbon cement clinker as well as preparation method and application thereof

    CN111925137A

  • High belite-calcium sulphoaluminate-calcium sulphosilicate cement clinker and preparation method thereof

    CN114213043A

  • Low-carbon high-strength micro-expansive cement clinker as well as preparation method and application thereof

    CN114538803A